Evolutionary Design of Radial Basis Function Neural Network for Data Modelling - Kaplan, Alparslan (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: In this thesis, implementation of Radial Basis a Function Neural Network (RBFNN) using genetic algorithm is described. The developed algorithm is used to model a certain dataset by training a RBFNN using some part of it, and then testing the performance of this RBFNN using the rest of data. The objective function of the proposed algorithm is to minimize the error between the computed output by the model and the target output given in the dataset. The genetic algorithm used in this thesis is an evolutionary algorithm that uses natural evolutionary process for selection and reproduction. An individual is constructed from the RBFNN parameters, which are hidden units, centers, weights, widths and bias associated with hidden units and output of RBFNN. Therefore, the fitness values are also assigned to all chromosomes as a result of getting the difference between the target output and the computed output by the RBFNN, in which a Gaussian function was used as an activation function. In experimental results, different tests were conducted in order to see the performance and correctness of the developed model. Since the number of hidden units plays an important role as well as weights, the intervals of weight values were adjusted accordingly and the number of hidden units was changed for different tests. As a result of conducted experiments, it is observed that the developed algorithm is successful in obtaining good results by minimizing the error. Keywords: Evolutionary algorithms, Radial Basis Functions, Data Modeling. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu tezde Radyal Tabanlı Fonksiyonlar Ağı (RTFA), genetik algoritması kullanılarak tasarımlanmıştır. Geliştirilen algoritma modellenmesi hedeflenen belirli bir veri kümesinin bir kısmını öğretme geri kalan kısmını test için kullanmaktadır. Geliştirilen algoritmanın amaç fonksiyonu bulunan model ile verilen hedef çıktı arasındaki hatayı en aza indirmektir. Bu tezde kullanılan genetik algoritma bir evrimsel algoritmadır. Bu genetik algoritmadaki bireyler RTFA parametrelerinden oluşturulmuştur: gizli birimler, merkezler, ağırlıklar, genişlikleri ve sapma. Bireylere verilen uygunluk değeri olarak, bulunan model ile verilen hedef çıktı arasındaki fark kullanılmaktadır. RTFA’nın gizli birimlerinde aktivasyon işleri olarak Gauss işleri kullanılmıştır. Deney sonuçlarında, geliştirilen modelin performans ve doğruluğunu kontrol etme amaçlı farklı testler uygulanmıştır. Deneysel sonuçları elde ederken RTFA parametrelerinden en önemli iki parametre olan gizli birimlerin sayısı ve ağırlıkların değerleri değiştirilmiş ve sonuçlar gözlemlenmiştir. Deneysel sonuçlar neticesinde geliştirilen uygulamanın, iyi sonuçlar bulma ve hatayı en aza indirmede başarılı bir yöntem olduğu tespit edilmiştir. Anahtar Kelimeler: Evrimsel algoritmalar, Radyal Tabanlı Fonksiyonlar Ağı, Veri Modelleme.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2012. Supervisor: Assist. Prof. Dr. Adnan Acan.
Keywords: Computer Engineering; Neural Networks (Computer Science); Evolutionary Computation; Evolutionary Algorithms - Radial Basis Functions - Data Modeling